Influência da qualidade da água no controle químico da mosca minadora do meloeiro, em Mossoró - RN - Moura Filho, Edmondson Reginaldo (Universidade Federal Rural do Semi-Árido, 2006)
The objective of this study was to evaluate the influence of water quality utilized for insecticides application in the chemical control of the melon leafminer. The study was carried out in three stages: 1 - Evaluation of the type of water (application with mineral water and water from the farm); 2 - Evaluation of the influence of different water pH levels (applications with mineral water with pH 6.0, pH 4.5 and pH 3.2); 3 - Evaluation of the influence of the application of mineral water diluted insecticides on plants infested in laboratory. The two first stages were carried out at Santa Julia Farm s production area, in Mossoró-RN. The insecticides utilized in all the stages were cyromazine, abamectin, chlorfenapyr, spinosad and acetamiprid. In the first stage, for each treatment, 10 infested leaves (one for each plant) were selected and in each leaf a number of leafminer larvae were encircled with a permanent;the insecticides were applied according to each assigned treatment; counts for live and dead larvae were performed two days after insecticide sprayings. In the second stage, larvae were marked as in the first stage and the insecticides diluted in mineral water (three pH levels) were applied; the numbers of larvae were counted two days after insecticide sprayings. In the third stage, the insecticides were diluted in mineral water (pH 6.0) and sprayed on previously infested plants maintained in laboratory; daily evaluations began twenty-four hours after insecticide application by counting of both alive and dead larvae. Data were analyzed and it was concluded that the type of water had no influence on the efficiency of the applied insecticides. The highest leafminer larvae mortality rates were obtained with the applications of cyromazine, abamectin and spinosad
Influence of the water quality on the chemical control of melon leafminer in Mossoró-RN
Keywords: Chemical control; Fly miner; Meloeiro culture region Mossoró; Controle químico; Mosca minadora; Meloeiro cultura região Mossoró; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA